2023
DOI: 10.5757/asct.2023.32.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Application of 3D Bioprinting Technology for Tissue Regeneration, Drug Evaluation, and Drug Delivery

Abstract: To overcome the limitation of two-dimensional cell culture not being able to mimic the in vivo microenvironment, three-dimensional (3D) bioprinting technology for 3D cell culture has emerged as an innovative culture platform. 3D bioprinting technologies can be divided into five types: inkjet-based bioprinting, extrusion-based bioprinting, stereolithography bioprinting, laser-assisted bioprinting and digital laser processing-based bioprinting technology. The 3D printing strategies achieved through a combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
(91 reference statements)
0
7
0
Order By: Relevance
“…PU and PVA materials are extensively known as biocompatible materials. 39 Previously, many reports have shown that PVA nanofiber-cultured HaCaT cells were nontoxic, and PVA had excellent cytocompatibility. 40 Additionally, Hong et al reported that the cell viability levels of PU nanofibers cultured on HaCaT cells used in wound dressing materials increased continuously over 7 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PU and PVA materials are extensively known as biocompatible materials. 39 Previously, many reports have shown that PVA nanofiber-cultured HaCaT cells were nontoxic, and PVA had excellent cytocompatibility. 40 Additionally, Hong et al reported that the cell viability levels of PU nanofibers cultured on HaCaT cells used in wound dressing materials increased continuously over 7 days.…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrated that the developed NFs could be applied to the skin to detect GHB. PU and PVA materials are extensively known as biocompatible materials . Previously, many reports have shown that PVA nanofiber-cultured HaCaT cells were nontoxic, and PVA had excellent cytocompatibility .…”
Section: Resultsmentioning
confidence: 99%
“…These bioinks are cell-encapsulating biomaterials used in the 3D printing process and must be friendly to both the printing process and 3D cell culture. Bioinks are also being designed to hold growth factors and exhibit thermo-responsive properties [52], which are critical for applications in bone regeneration and drug delivery [53], as well as the incorporation of sensor units [50]. The active materials in bioinks can serve as an extracellular matrix that helps provide adhesion to cells, the proliferation of cells, and cellular differentiation after bioprinting.…”
Section: Bio-inksmentioning
confidence: 99%
“…Nanomaterials-based bioinks have gained popularity for 3D bioprinting due to their ability to address the constraints of non-nanomaterials bioinks, such as high printability, mechanical stability, and biocompatibility. There are two categories of nanomaterials bioinks: Nanomaterials-based hybrid and other bioinks contain natural and synthetic polymeric nanomaterials, while other bioinks consist of either natural or synthetic nanomaterials . Nanomaterials-based hybrid bioinks are becoming increasingly popular because of their improved biocompatibility and mechanical properties.…”
Section: Nanomaterials-based Hybrid Bioinksmentioning
confidence: 99%
“…The advent of three-dimensional (3D) bioprinting methodology stands as a profoundly consequential and revolutionary facet within the realm of additive biomanufacturing (ABM) strategies, offering a potential remedy to the scarcity of organ donors prevalent in the field of tissue engineering. The ABM methodology is rooted in the principles of 3D printing technology, whereby biomaterials encompassing cellular and biomolecular constituents have been harnessed as bioinks in the process, ,, added to manufacture 3D functional living objects such as tissues, organs, and other artificial biological parts layer-by-layer. ,,, This technology boasts an expansive array of biomedical applications, encompassing orthopedic, cardiovascular, cutaneous, osteochondral, dental, and assorted soft-tissue engineering realms, including but not limited to pancreatic and hepatic tissue engineering applications . Historically, during the year 1988, Klebe et al repurposed an inkjet printer to deposit cellular bioink, marking a pioneering instance of biological component fabrication on 2D surfaces. , Charles Hull created stereolithography, the first 3D bioprinting method, in 1986. , Subsequently, 3D patterned cells with a few micrometers in height were printed in 1999 by Odde et al In contrast, Sachs et al pioneered multilayered 3D printed biological structures using a chemical scaffold in 1990, followed by significant advancements by the early 20th century .…”
Section: Introductionmentioning
confidence: 99%